Drought tolerance in Brassica napus is accompanied with enhanced antioxidative protection, photosynthetic and hormonal regulation at seedling stage. Issue 2 (5th March 2021) - Ayyaz, Ahsan; Miao, Yilin; Hannan, Fakhir; Islam, Faisal; Zhang, Kangni; Xu, Jianxiang; Farooq, Muhammad Ahsan; Zhou, Weijun
Abstract: Climate change, food insecurity, water scarcity, and population growth are some of today's world's frightening problems. Drought stress exerts a constant threat to field crops and is often seen as a major constraint on global agricultural productivity; its intensity and frequency are expected to increase in the near future. The present study investigated the effects of drought stress (15% w/v polyethylene glycol PEG‐6000) on physiological and biochemical changes in five Brassica napus cultivars (ZD630, ZD622, ZD619, GY605, and ZS11). For drought stress induction, 3‐week‐old rapeseed oil seedlings were treated with PEG‐6000 in full strength Hoagland nutrient solution for 7 days. PEG treatment significantly decreased the plant growth and photosynthetic efficiency, including primary photochemistry (Fv/Fm) of PSII, intercellular CO2, net photosynthesis, chlorophyll contents, and water‐use efficiency of all studied B. napus cultivars; however, pronounced growth retardations were observed in cultivar GY605. Drought‐stressed B. napus cultivars also experienced a sharp rise in H2 O2 generation and malondialdehyde (MDA) content. Additionally, the accumulation of ROS was accompanied by increased activity of enzymatic antioxidants (superoxide dismutase, peroxidase, catalase, ascorbate peroxidase, glutathione reductase, and monodehydroascorbate reductase), although the increase was more obvious in ZD622 and ZS11. Drought stress also caused an increased endogenous hormonal biosynthesis (abscisic acid, jasmonic acid, salicylic acid) and accumulation of total soluble proteins and proline content, but the extent varies in B. napus cultivars. These results suggest that B. napus cultivars have an efficient drought stress tolerance mechanism, as shown by improved antioxidant enzyme activities, photosynthetic and hormonal regulation.